The right to work in the context of human rights: a perspective of Joaquin Herrera flores’ critical theory - Boryca, Marynara; Furtado, Lana; Weinhardt De Oliveira, Silvana (Seven Editora, 2023)
Faced with the historical process of human rights and the struggle for the dignity of the human person, the right to work emerges as a regulation of the employment relationship as a guarantee of access to indispensable resources for the survival of the individual and access to goods. In addition, it extends to the need to guarantee decent working conditions, seeking to protect the worker from the violation of rights. In this sense, this article seeks to reflect on labor law in its intersection with human rights, based on the critical theory of Joaquin Herrera Flores. DOI: 10.56238/pacfdnsv1-055